Phytosociological Studies of the Ground Flora in Different Types of Vegetation on Tiger Hill, Darjeeling District, West Bengal - Das, A. P.; Lahiri, A. X. (Indian Forester, 1997)
A large part of Tiger Hill forest (Darjeeling, West Bengal) was clearfelled in the first decade of this century and a part of it was planted with Cryptomeria japonica (L.f.) D. Don in 1921. Now there exists three types of vegetation side by side: (i) Natural Forest, (ii) Plantation Forest and (iii) Grassland. Phytosociological studies were made to understand the differences in the ground covering vegetation within these vegetational types and to understand tbe Relative Density, Relative Frequency and Importance Value of its elements. Altogether 85 species and 3,672 individuals were recorded from just 15 one-square meter quadrats. While 33.33% species were same between Natural Forest and Plantation Forest, it is only 7.25% between Natural Forest and Grassland and 13.84% between Plantation Forest and Grassland. Theropbytes (40%) appeared to be a most successful lifeform, but Chamaephytes (24.7%) were also well represented along witb 14.12% Cryptophytes, 12.94% Hemicryptophytes and 8.23% Phanerophytes. Most of the 31 species of angiosperm recorded from the Plantation Forest were sparsely distributed, feeble and produced only few or no flowers. A more spaced plantation of Cryptomeria japonica mixed with selected broad-leaved non-resinous trees has heen suggested here to improve the picture. However, all species recorded from Natural Forest (37 spp.) and Grassland (43 spp.) were normal in their development and reproduction though were much affected with grazing.